Data and digital rights: recent Australian developments - Gerard Goggin; Ariadne Vromen; Kimberlee Weatherall; Fiona Martin; Lucy Sunman (Internet Policy Review)
Data privacy rights is one of the most urgent issues in contemporary digital policy. In the face of insurgent citizen activism and outcry, national governments are looking for options to address this problem - something difficult for many jurisdictions when they lack robust, responsive policy frameworks, even in the wake of the call to act represented by the European General Data Protection Regulation (GDPR). In this paper we explore two Australian developments in 2018-2019 which take up the challenge: proposals from the Australian Competition and Consumer Commission (ACCC)’s Digital Platforms Inquiry to more stringently regulate social media companies when it comes to data privacy; and the government-mandated creation of a Consumer Data Right. Both policy initiatives seek to grapple with the widening pressure to provide better public domain information, fair and effective options for users to exercise choice over how they configure technologies, and strengthened legal frameworks, enhanced rights, and better avenues redress. However, in our analysis, we find little evidence that the initiatives are joined up, or connected by any common goal of really understanding, or acting on, citizen concerns to do with data privacy threats.